The common value and uniqueness theorems of algebroid functions - Chai, Fujie; Gao, Zongsheng (Global Journal of Mathematical Analysis, 2015)
In this paper, we investigate the common values and growth relationship between two algebroid functions and prove several growth theorems involving common values. Moreover, on this basis, we study uniqueness theory of algebroid function and prove several elegant uniqueness theorems.